A compact rail-to-rail CMOS buffer amplifier with very low quiescent current - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2015)
In this work, a very compact, rail-to-rail, high-speed buffer amplifier for liquid crystal display (LCD) applications is proposed. Compared to other buffer amplifiers, the proposed circuit has a very simple architecture, occupies a small number of transistors and also has a large driving capacity with very low quiescent current. It is composed of two complementary differential input stages to provide rail-to-rail driving capacity. The push-pull transistors are directly connected to the differential input stage, and the output is taken from an inverter. The proposed buffer circuit is laid out using Mentor Graphics IC Station layout editor using AMS 0.35 mu m process parameters. It is shown by post-layout simulations that the proposed buffer can drive a 1nF capacitive load within a small settling time under a full voltage swing, while drawing only 1.6 mu A quiescent current from a 3.3V power supply.
Keywords: rail-to-rail; quiescent current; slew rate; buffer amplifier; liquid crystal display; settling time; CLASS-B BUFFER; LCD; DRIVER